The Analysis of Cell Phone Usage among Medical Students in UCMS, Bhairahawa, Nepal - Maddheshiya, Nisha; Rastogi, Varun; Gautam, Vanita; K, Nishant (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: The smartphones have become an integral part of human’s life. It combines different sophisticated features that allow users to keep pictures, memories, personal information, correspondence, health and financial data in one place. The phones allow people to maintain continuous communication without interruption of their movements and distances. Smartphones and handheld devices (HHD) combine advanced computing capability, such as internet communication, information retrieval, video, e-commerce and other features, that makes the device one of the indispensable requirements for many people. MATERIAL AND METHODS: The research work was carried out to understand and also find correlation between excess usage of cell phones and its impact on human health. The study incorporates structured questionnaire administered to 200 medical students of their knowledge with the data obtained and statistically analyzed during the course of the study. RESULTS: Our findings indicated that students are influenced negatively by mobile phones because attention is focused on chatting, music, surfing, entertainment and movies neglecting their health that has an impact on their physical and psychological status, which directly relates to the duration of usage of phone. CONCLUSION: Mobile phone is one of the technologies of present era. It has both positive and negative impact on society. However, addiction and huge reliance on cell phones carry risks on human development and health. The current study highlights potential risks that cell phones can cause to medical students and the negative impact it has on their health status.